The impact of sevoflurane anesthesia on postoperative renal function: a systematic review and meta-analysis of randomized-controlled trials. - RV Sondekoppam; KH Narsingani; TA Schimmel; BM McConnell; K Buo; TJP Ozelsel (Can J Anaesth., 2020)
Purpose: Renal damage secondary to fluoride ions and compound A (CpdA) after sevoflurane anesthesia remains unclear. For safety reasons, some countries still recommend minimum fresh-gas flows (FGFs) with sevoflurane. We review the evidence regarding the intraoperative use of sevoflurane for anesthesia maintenance and postoperative renal function compared with other anesthetic agents used for anesthetic maintenance. Secondarily, we examine the effects of peak plasma fluoride and CpdA levels and the effect of FGF and duration of anesthesia on these parameters. Source: The databases of MEDLINE (OVID and Pubmed), EMBASE, the Cochrane Library, Health Technology Assessment Database, CINAHL, and Web of Science were searched from inception until 23 April 2020 to identify randomized-controlled trials (RCTs) in humans utilizing sevoflurane or an alternative anesthetic for anesthesia maintenance with subsequent measurements of renal function. Two different paired reviewers independently selected the studies and extracted data. The quality of the evidence was appraised using GRADE recommendations. Principal findings: Of 3,766 publications screened, 41 RCTs in human patients were identified. There was no difference between creatinine at 24 hr (21 studies; n = 1,529), or creatinine clearance (CCR) at 24 hr (12 studies; n = 728) in the sevoflurane vs alternative anesthetic groups. Peak fluoride and fluoride measured at 24 hr were higher with sevoflurane compared with other inhaled anesthetics. Subgroup analyses for sevoflurane usage in various contexts showed no significant difference between sevoflurane and alternative anesthetics for creatinine or CCR at 24 hr at varying FGF, duration of exposure, baseline renal function, or absorbent use. Conclusions: We did not find any association between the use of sevoflurane and postoperative renal impairment compared with other agents used for anesthesia maintenance. The scientific basis for recommending higher FGF with the use of sevoflurane needs to be revisited. Keywords: compound A; fluoride ions; fresh-gas flow; nephrotoxicity; sevoflurane.